Asymmetric transition metal-catalyzed alkyl addition to imines with chiral phosphine ligands - El Hajjaji, Samir (2010)
The research project presented in this thesis deals with the development of the alkylation of protected aldimines using organoaluminium and organozinc compounds as alkylating agents. To this end, efforts have been focused into the methylation reaction using trimethylaluminium and dimethylzinc. It was hoped to establish promising conditions using the methylate group and then to extend the catalytic system to other interesting nucleophiles. In the case of organoaluminium alkylation the reaction was extended to other nucleophiles, namely to the allyl and propargyl groups. The identificaton of suitable metal catalysts as well as diphosphine ligands was carried out by means of extensive high throughput screening. On the one hand [IrCl(COD)]2 proved to be very efficient when associated to AlMe3 or DABAL-Me3 in the non-enantioselective 1,2-addition reactions to aldimines (100% conversion in 3 h). On the other hand, [RhCl(COD)]BF4 was found to be able to efficiently catalyse the enantioselective 1,2-addition of Me2Zn to aldimine substrates (100% conversion in 3 h - up to 99% e.e.). A preliminary screening of a range of aldimines bearing different protecting groups aimed at selecting the most interesting substrate in terms of reactivity and ease of cleavage of the protecting group. Once this substrate had been identified, a range of derivatives was synthesised in order to appraise the scope of the newly developed reaction. The diphenylphosphinoyl (dpp) protecting group turned out to be the best activating group for aldimines tested within the framework of this study. In addition to being easy to introduce, the dpp group can also be removed easily under mild conditions. What is more, the presence of a phosphorus atom on this protecting group is a feature which was used to determine the enantiomeric excess by 31P NMR spectroscopy, thus providing a novel and efficient screening tool at disposal. In the course of this investigation, various issues were faced and tackled. One of them was the unexpected non-reproducibility taking place in the Rh-catalysed Me2Zn addition reaction; however, a deeper thinking of the reaction mechanism enabled us to solve this problem to eventually get a more robust catalytic system. Another one was the formation of a reduction product as a by-product of the Rh-catalysed Me2Zn addition reaction. Finally, several interesting attempts (Et2Zn addition, aliphatic imine synthesis), findings (effect of ligand bite angle) and hypotheses (testing of the BPM ligand) made during this study deserve to be studied further for improvement and optimisation.